Color-tuning Pt(ii) complexes for natural-light electrophosphorescence. Issue 4 (4th January 2022) - Wu, D.; Qin, K.; Gao, X.; Cheng, S.; Wu, A.; Sha, C.; Ma, H.; Sun, Z.; Zhang, C.; Hang, X.-C.
Abstract : Efficient and durable OLEDs of cyan, greenish yellow, yellow and white colors were fabricated in simple structures with Pt–Cpy bonded complexes, giving state-of-the-art tuning the color of electroluminescence. Abstract : Two cyclometallated Pt(ii ) complexes with Pt–Cpy bonded tetradentate ligands, Pt(pzpy-czOpy) and Pt(pzpy-czcl), have been fully investigated, showing that a simple strategy that reduced torsion could properly direct towards broad spectrum emission. Details in the photo- and electro-luminescence reveal entirely different types of localized emissions for the two complexes as well as their color tunability in devices. Luminescence of the complex responds to the mode of photo- or electro-excitation, resulting in different radiative relaxation process and also their emission spectra. Efficient and durable broad-spectrum OLEDs of cyan, greenish yellow, yellow and white colors were fabricated with simple structures, giving state-of-the-art performance in tuning the emission for natural color electroluminescence.